ANALYSIS OF FACTORS AFFECTING PURCHASING BEHAVIOR THROUGH E-COMMERCE AMONG BUYERS IN THE EAST WONGKADITI VILLAGE OF GORONTALO CITY - Rizal; Ismail Tahir; Habibah Abuba (Journal of Economic, Business, and Administration (JEBA), 2023)
ABSTRACT Habibah U. Abuba. NPM. 1320192002. 2021. Analysis of Factors Affecting Purchasing Behavior through E-commerce among Buyers in the East Wongkaditi Village of Gorontalo City. Undergraduate Thesis, Advisor I: Rizal S.E., M.Si., and Advisor II: Ismail Tahir S.Pd., M.Pd. Bachelor of Business Administration, Faculty of Economics and Business of Universitas Bina Mandiri Gorontalo. This research aims to analyze factors that influence people's behavior in making purchases online or through E-commerce in the community of Wongkaditi Village East of Gorontalo City. The method in this study uses a qualitative approach by conducting interviews with 7 people as respondents in the study, with some questions to find out the factors that can influence people's buying behavior online. Data analysis techniques in this study use univariate analysis which is an analysis that is done by analyzing each variable from the research framework. The results showed that people who choose to make purchases online or through E-commerce because it is influenced by the ease and price of goods offered by online sellers that are different from the price of goods purchased directly at the nearest store. Other factors that also affect online buying behavior in the community are the state of the environment around the community and information provided by online sellers that can attract people to make online purchases.